On a Subclass of Meromorphic Functions Defined by Hilbert Space Operator. (18th June 2013) - Rosy, Thomas; Varma, S. Sunil
Abstract : In this paper, we define a new operator on the class of meromorphic functions and define a subclass using Hilbert space operator. Coefficient estimate, distortion bounds, extreme points, radii of starlikeness, and convexity are obtained.